The Pesantren Network in Samarinda - Khojir (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2016)
The aim of this research is to reveal the model, the consistency, and the implication of pesantren network in Samarinda. This is a qualitative research based on sociology, phenomenology, and educational approach. The research was conducted within the total of 37 pesantren in Samarinda which were chosen based on their geographical sites, genealogical aspect, scientific affinity, as well as their tendency toward certain social organization. The geographical network consists of pesantren in South Kalimantan, South Sulawesi, East Java, Central Java, and Jambi. The result shows that this kind of network bears two forms namely direct genealogy and family relationship. Meanwhile, the network of social organization entails pesantren of Nahdlatul Ulama (NU), Muhammadiyah, LDII, Jama’ah Tabligh, and Suffah Hizbullah. Furthermore, the network of scientific affinity comprises language science, physical/martial art, and sanad Al-Qur’an. The model of the pesantren network is established through pesantren alumnae’s journey into new places or by Islamic preaching, alumni empowerment, cadres’ regeneration, and service. The degree of consistency is categorized into three levels, namely, consistent, inconsistent, and modification. This network contributes to the development of pesantren and society in Samarinda.